2007
DOI: 10.1038/ncpendmet0647
|View full text |Cite
|
Sign up to set email alerts
|

The replication of β cells in normal physiology, in disease and for therapy

Abstract: Replication of beta cells is an important source of beta-cell expansion in early childhood. The recent linkage of type 2 diabetes with several transcription factors involved in cell cycle regulation implies that growth of the beta-cell mass in early childhood might be an important determinant of risk for type 2 diabetes. Under some circumstances, including obesity and pregnancy, the beta-cell mass is adaptively increased in adult humans. The mechanisms by which this adaptive growth occurs and the relative cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
217
0
6

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 255 publications
(229 citation statements)
references
References 81 publications
2
217
0
6
Order By: Relevance
“…In healthy individuals, pancreatic beta cell mass is dynamically maintained throughout life by homeostatic regulation that balances ongoing processes of neogenesis and beta cell death [37,38]. In patients with type 2 diabetes, there is, over time, a progressive loss of beta cells due to increased apoptosis [39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…In healthy individuals, pancreatic beta cell mass is dynamically maintained throughout life by homeostatic regulation that balances ongoing processes of neogenesis and beta cell death [37,38]. In patients with type 2 diabetes, there is, over time, a progressive loss of beta cells due to increased apoptosis [39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…Increased demand for insulin with increased insulin resistance/obesity would lead to a larger beta cell population; failure to expand beta cell number by replication and neogenesis and/or increased apoptosis would result in type 2 diabetes [8,9]. An increase in the beta cell population with increased demand for insulin in obesity is very evident in rodents [10] but is smaller and variable in obese humans [11,12]. The half-life of beta cells has been estimated to be 30-60 days in young rodents (<1 year old) on the basis of histological quantification of apoptotic and neogenic cells [9].…”
Section: Introductionmentioning
confidence: 99%
“…27 Furthermore, GSK-3 inhibitors, due to their proliferation-promoting abilities, may be suitable in combination with immunosuppressive agents for treatment of T1DM patients because studies suggest that in most cases, even those with long-standing T1DM, some b-cells persist and are continually destroyed and also because of enhanced b-cell formation in T1DM. 1,3,45 …”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…1,2 In T1DM, b-cell mass is reduced due to autoimmune-mediated b-cell destruction and accumulating data from clinical studies and animal models suggest increased b-cell formation in T1DM. 1,3 T2DM, the most common form, is characterized by relative reductions in b-cell mass, b-cell dysfunction and peripheral insulin resistance. 4 Several studies have demonstrated that replication of pre-existing differentiated b-cells plays an important role in regulating expansion and maintenance of postnatal/adult b-cell mass.…”
Section: Introductionmentioning
confidence: 99%